2022
DOI: 10.1183/23120541.00186-2022
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the frequency of obstructive sleep apnoea syndrome in patients with subclinical hypothyroidism

Abstract: BackgroundThe aim of this study is to determine the frequency of Obstructive Sleep Apnea Syndrome (OSAS) in a study group with the diagnosis of subclinical hypothyroidism and in a control group without the diagnosis of subclinical hypothyroidism. This study compares these two groups in terms of demographic characteristics, chronic diseases, and especially polysomnographic data.MethodsA total of 120 patients were included in this study. They consistedof 60 patients with newly diagnosed subclinical hypothyroidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For example, Feng et al, 12 found that TSH levels, serum-free triiodothyronine (FT3), and FT4 did not significantly affect children with obstructive sleep apnea-hypopnea syndrome (OSAHS) before and after endoscopic adenoidectomy. This was also documented by the studies done in USA 25 and in Turkey, 26 wherein OSA showed no significant relationship with subclinical or prior hypothyroidism.…”
Section: Discussionmentioning
confidence: 54%
“…For example, Feng et al, 12 found that TSH levels, serum-free triiodothyronine (FT3), and FT4 did not significantly affect children with obstructive sleep apnea-hypopnea syndrome (OSAHS) before and after endoscopic adenoidectomy. This was also documented by the studies done in USA 25 and in Turkey, 26 wherein OSA showed no significant relationship with subclinical or prior hypothyroidism.…”
Section: Discussionmentioning
confidence: 54%
“…However, the association between SH and sleep disturbances has not been unequivocally reported in the literature. For instance, the study by Gencer et al (2022) included 120 participants, of whom 60 had newly diagnosed SH and 60 had normal thyroid functions; the authors did not detect any significant difference in the frequency and severity of obstructive sleep apneas measured by polysomnography ( Gencer et al, 2022 ). The absence of group differences in an indirect index of sleep-related breathing disorders, as provided by SBD scale scores of the SDSC, could be explained by two reasons.…”
Section: Discussionmentioning
confidence: 99%